2002
DOI: 10.1007/s101620020028
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Noise-Induced Cellular Injury and Repair in the Mouse Cochlea

Abstract: To assess the dynamics of noise-induced tissue injury and repair, groups of CBA/CaJ mice were exposed to an octave-band noise for 2 hours at levels of 94, 100, 106, 112, or 116 dB SPL and evaluated at survival times of 0, 12, 24 hours or 1, 2, or 8 weeks. Functional change, assessed via auditory brainstem response (ABR), ranged from a reversible threshold shift (at 94 dB) to a profound permanent loss (at 116 dB). Light microscopic histopathology was assessed in serial thick plastic sections and involved quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

47
458
3
10

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 486 publications
(518 citation statements)
references
References 19 publications
47
458
3
10
Order By: Relevance
“…The present report concerns loss of type IV fibrocytes in mice following noise exposure as a model for at least part of unexplained cell loss in the spiral ligament of humans. This work extends a previous study that showed type IV fibrocytes to have a surprisingly low threshold for noise-induced destruction (Wang et al 2002). In the present report, cytochemical traits that are useful for distinguishing type IV fibrocytes from nearby cells and for revealing physiological traits of these cells are presented.…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…The present report concerns loss of type IV fibrocytes in mice following noise exposure as a model for at least part of unexplained cell loss in the spiral ligament of humans. This work extends a previous study that showed type IV fibrocytes to have a surprisingly low threshold for noise-induced destruction (Wang et al 2002). In the present report, cytochemical traits that are useful for distinguishing type IV fibrocytes from nearby cells and for revealing physiological traits of these cells are presented.…”
Section: Introductionsupporting
confidence: 88%
“…Loss or damage to spiral ligament cells following acoustic trauma in animals has been reported (Johnsson and Hawkins 1976;Liberman and Kiang 1978;Wang et al 2002;Hirose and Liberman 2003;Ohlemiller and Gagnon 2007). The present report concerns loss of type IV fibrocytes in mice following noise exposure as a model for at least part of unexplained cell loss in the spiral ligament of humans.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…This is a point in time where noise-induced damage to afferent terminals at inner hair cells is usually at a maximum (Lin et al 2011). It is therefore unlikely that mechanisms usually associated with common noise-induced temporary threshold shifts (Robertson 1982(Robertson , 1983Wang et al 2002) are responsible for the tinnitus-like sensations observed during the BP.…”
Section: Lf Sound-induced Transient Sound Perceptionsmentioning
confidence: 99%
“…Nevertheless, damage within the inner ear is most likely to contribute. Noise trauma can have a range of chronic effects, such as stereocilia damage, loss of OHCs and IHCs, complete loss of the organ of Corti, and many more, with differences in spatial distribution, time course, and dependence on noise level (and presumably exposure duration) (e.g., Saunders et al 1985;Liberman 1987Liberman , 1990Wang et al 2002). …”
Section: Location Of Damages Captured By Altered Baseline and Gainmentioning
confidence: 99%